2023
DOI: 10.1099/ijsem.0.006121
|View full text |Cite
|
Sign up to set email alerts
|

Microbacterium nymphoidis sp. nov. and Microbacterium festucae sp. nov., two novel species with high plant-promoting potential isolated from wetland plants in China

Chunyi Li,
Xiaoqian Jin,
Fu Yang
et al.

Abstract: Two novel plant growth-promoting, rod-shaped, Gram-positive and non-motile rhizobacteria, W1NT and W2RT, were isolated from wetland plants Festuca elata and Nymphoides peltatum, respectively, in China. The results of the 16S rRNA sequence alignment analysis showed that they were related to Microbacterium , with the highest similarity to Microbacterium ketosireducens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…The genus contains Gram-reaction-positive, catalase-positive, non-endospore-forming, motile or non-motile, rod-shaped bacteria and is monophyletic based on single or a few core genes [3, 4]. The phylogenomic relationship of the genus, based on core and whole genomes, has been partially studied for fewer than 50 species in the description of new taxa [5–12], However, Nouioui et al [5] showed that the genus is paraphyletic in phylogenetic analysis using whole genomes, with some species being transferred to the genus Thermomonospora . Recently, Lee et al [13] performed overall phylogenomic clustering of the genus based on core-genome analysis of nearly all the genomes available in public databases.…”
Section: Introductionmentioning
confidence: 99%
“…The genus contains Gram-reaction-positive, catalase-positive, non-endospore-forming, motile or non-motile, rod-shaped bacteria and is monophyletic based on single or a few core genes [3, 4]. The phylogenomic relationship of the genus, based on core and whole genomes, has been partially studied for fewer than 50 species in the description of new taxa [5–12], However, Nouioui et al [5] showed that the genus is paraphyletic in phylogenetic analysis using whole genomes, with some species being transferred to the genus Thermomonospora . Recently, Lee et al [13] performed overall phylogenomic clustering of the genus based on core-genome analysis of nearly all the genomes available in public databases.…”
Section: Introductionmentioning
confidence: 99%